Dementia Mimicking Presentation in Normopressure Hydrocephalus: A Case Report - Noor Alia Susianti; Caroline Evanthe Nathania; Astuti Prodjohardjono; Abdul Gofir; Indarwati Setyaningsih; Cempaka Thursina Srie Setyaningrum; Sri Sutarni; Vega Pratiwi Putri (AKSONA, 2026)
Highlight: Normal pressure hydrocephalus (NPH) is characterized by gait apraxia, urinary incontinence, ventriculomegaly, and cognitive impairment that mimics dementia, potentially leading to misdiagnosis. Comprehensive assessment, including clinical examination, brain imaging, and CSF testing, is critical for distinguishing NPH from dementia. Early and prompt diagnosis and treatment of NPH are crucial for improving long-term outcomes.   ABSTRACT Introduction: Normal Pressure Hydrocephalus (NPH) can occur following Traumatic Brain Injury (TBI). It is characterized by ventricular enlargement and presents with a classic triad: gait apraxia, urinary incontinence, and cognitive impairment. Cognitive impairment in NPH often overlaps with other neurocognitive disorders, such as dementia, which frequently leads to misdiagnosis. Case: A 59-year-old man presented with progressive memory decline, bladder incontinence, and gait apraxia following a head trauma. A CT scan performed after the head trauma revealed an intracerebral hemorrhage in the right thalamus. One year later, the patient complained of gait disturbance, as well as urinary and fecal incontinence. His general examination was normal, but the neurological examination showed the presence of a primitive reflex, specifically, the glabellar sign—and the patient exhibited a gait apraxia, poor spontaneity, and slowed speech. Neurobehavioral assessment showed attention and orientation disturbances, sensory cortical aphasia, and dementia syndrome. A follow-up CT scan revealed cerebral atrophy with ventriculomegaly ex vacuo with cerebrospinal fluid leakage. The patient subsequently underwent ventriculoperitoneal shunt therapy, and the cognitive assessment score showed improvement after the procedure. Conclusion: Diagnosing an NPH remains challenging due to the overlap of its cognitive impairment symptoms with other neurocognitive disorders. Furthermore, the treatment response varies widely, posing a further obstacle for clinicians to effectively manage NPH patients. Although early and prompt diagnosis is crucial for successful therapy, it continues to pose a significant challenge for clinicians.